0482 A Preliminary Study on the Efficacy of Forehead-Cooling for Relieving Menopausal Sleep Difficulties and Hot Flashes. (27th May 2020) - Baker, F C; de Zambotti, M; Chiappetta, L; Nofzinger, E
Abstract: Introduction: Many women experience sleep difficulties in the approach to menopause and post-menopause, with about 25% experiencing severe symptoms that impact daytime functioning and quality of life. Hot flashes contribute to these sleep difficulties, being associated with nocturnal awakenings, poorer sleep quality, and chronic insomnia. New non-pharmacological sleep solutions have become available, including a forehead cooling device designed to target elevated brain metabolism in insomnia sufferers. Here, we explored whether this device was effective in improving subjective sleep and hot flashes in menopausal-age women with insomnia symptoms. Methods: This study was an open-label, in-home investigation of the efficacy of nightly treatment with a forehead cooling device in 20 women (55.1 ± 4.2 years) with insomnia symptoms and daily hot flashes. Participants completed daily diaries assessing sleep quality and hot flashes across a baseline week (no treatment) followed by 4 weeks of treatment. They also completed questionnaires before and after treatment including the insomnia severity index and the hot flash related daily interference scale. Results: Women reported better sleep quality with a shorter sleep onset latency and fewer awakenings (between 14-30% improvement) during the first week of device use, with further improvements over time, relative to baseline (p <0.001). Women also reported fewer nocturnal hot flashes that were less severe during treatment (p<0.001). They had lower insomnia severity scores post-treatment (9.3±5.8) compared to pre-treatment (20.0±5.7) (p<0.001), with 17 participants showing a reduction of 6 points or greater on the insomnia severity index. There was also a significant reduction in hot flash related daily interference post-treatment (p<0.001). Conclusion: Use of a forehead cooling device during the night improved subjective sleep quality and reduced insomnia symptoms and hot flash frequency and severity in this preliminary study of menopausal-age women. Further large scale randomized controlled trials are required to determine efficacy. Support: Ebb Therapeutics